Do the deputies we vote legislate? Analizing the proportionality of the Costa Rican electoral system in the legislative elections (2002 – 2022) - Molina Ramírez, Alejandro (2024)
This article quantifies the disproportionality in the Costa Rican legislative elections of 2002, 2006, 2010, 2014, 2018 and 2022. In other words, evaluates the distribution of seats according to the votes won by each political party (Lijphart 1994, Shugart and Taagepera 2018) that took part of the legislative ballot in this temporal delimitation. Based on the disaggregation of the data by electoral districts in each electoral process, this article analyzes the main features of the electoral system and their influence on the disproportionality index.